Assessment of Oral Health Behavior and Gingival Status among Dental Undergraduate Students in a Dental College in Bangalore - Reji, Anagha; Murali, R.; A, Shamala.; Yalamalli, Mansi; N, Pradeep; GM, Suchetha (International Journal Of Drug Research And Dental Science, 2023)
Introduction: Oral health is a critical but overlooked component of overall health and well-being among children and adults. Behavioural and social factors significantly impact oral health. Dental health professionals have an important role in the improvement of the public’s health education level. Therefore, the acquisition of their status regarding oral health behaviour and gingival health during the future dentist’s training period is very important. Aim: to assess the oral health behaviour and gingival status of undergraduate dental students in a dental college in north Bangalore. Methodology: A cross-sectional study was conducted to assess the oral health behaviour and gingival status of undergraduate dental students in a dental college. The study population consisted of a total of 210 dental students who were administered. structured questionnaire for dental behaviour titled “Hiroshima University-Dental Behavioral Inventory” (HU-DBI). Gingival status was assessed by measuring Full Mouth Plaque Score (FMPS), Full mouth Bleeding Score (FMBS), and Papillary Bleeding Index. (PBI). Results: This survey shows that the knowledge regarding the importance of brushing and oral hygiene maintenance increases as students advance in their dental courses. A statistically significant (p-value < 0.05) relationship between FMBS and PBI and dental health behaviour of participants is seen. Conclusion: The results of oral health behaviour and gingival status of dental students reveal that there exists a positive association between oral health and gingival health of the students and that as years pass in dental school students tend to care more and have a positive impact towards dental health.